Respuestas
Respuesta dada por:
1
Respuesta:
5x-11=7+2x
5x-2x=7+11
3x=18
x=18/3
x=6
COMPROBACIÓN:
5(6)-11=7+ 2(6)
19=19
-8x-7=-6x+1
-8x+6x=1+7
-2x=8 (· -1)
2x=-8
x=-4
COMPROBACIÓN:
-8(-4)-7= -6(-4) +1
32-7= 24+1
25=25
9x+2 ≥ 6+7x
9x-7x ≥ 6-2
2x ≥ 4
x ≥ 2
5x-9 ≥ 8x+6
5x-8x ≥ 6+9
-3x ≥ 15 (· -1)
3x ≤ -15
x ≤ -5
Adjuntos:
![](https://es-static.z-dn.net/files/d9c/3c19913c2f5f8c884c94320484dde2c3.png)
is12mar:
todo eso es de poner
Preguntas similares
hace 5 años
hace 8 años
hace 8 años
hace 9 años
hace 9 años